Assistance in Writing Problem-Based Semester Learning Plans and Projects for Lecturers - Fitriawan, Dona; Yani T, Ahmad; Hartoyo, Agung; Siregar, Nurfadilah; Yusmin, Edy; Mirza, Ade; Nursangaji, Asep; Sugiatno, Sugiatno; Jamiah, Yulis; Saputra, Rachmat (International Journal of Public Devotion, 2024)
This dedication began with discussions between lecturers at two institutions discussing independent learning which was proclaimed by the Ministry of Research, Technology and Higher Education to be precise in February 2022 with a discussion agreement in the form of understanding the new curriculum and working together to develop learning tools by adapting the characteristics of the new curriculum. One of the goals that needs to be presented in learning tools is the inclusion of strengthening character education in an effort to build the realization of the Pancasila profile and its six dimensions. This service was held at UNU West Kalimantan with the form of implementation in the form of assistance in writing model-based learning semester learning design tools or case studies. The practice of using it uses the steps: 1) identification of general and specific problems in learning; 2) formulate various learning outcomes; 3) determine the required assessment tools; 4) develop a new curriculum learning process; 5) pouring the flow of learning objectives into lesson plans. With the results of the dedication, namely: 1) assisting in writing the rps until it is finished; 2) rps that is documented as a reference for the learning process; The formation of the draft RPS which was later ratified as an RPS guide at UNU West as one of the basic learning tools.